Innovations in teaching L2 writing: How changes in teachers' SCK and PCK impact learners' perceptions and writing outcomes. (June 2022) - Shi, Leimin; Baker, Amanda
Abstract: Learners' perceptions of their teachers' practices have received considerable research attention due to their impact on both teacher development and students' learning outcomes. However, students' perceptions of their teachers' knowledge have rarely been explored. This qualitative study investigates: 1) students' perceptions of changes to their teachers' knowledge of subject matter (SCK) and pedagogical content (PCK) about writing instruction, and 2) how such changes impact students' (perceptions of good) writing outcomes. To achieve these aims, six experienced university teachers in China attended workshops, which introduced them to a Systemic Functional Linguistics (SFL)-informed genre approach for teaching writing. The teachers then implemented this approach in their classes. Thirty students from the teachers' classes subsequently participated in focus group interviews about their perceptions of potential changes to their teachers' SCK and PCK as a result of the workshop series. Nine sets of writing samples, consisting of students' pre- and post-workshop writing samples, were also collected to address the second aim. Overall, findings showed that students perceived changes to their teachers' SCK and PCK positively and that students' writing outcomes also improved. This study has implications for both the application of SFL genre approach in EFL contexts and second language teacher professional development.